Print media design through feminism approaches / Pibool Waijittragum and Palang Wongtanasuporn - Waijittragum, Pibool; Wongtanasuporn, Palang (2019)
This research aims to study the suitable content and layout design of print media which focuses on female’s interest through feminist theory. This research has been conducted as a qualitative research with semi-structured questionnaires. The interview has been made with 14 editors of different printed materials for women in order to obtain information on popular content, proper styles and design elements for the layout. It is found that popular contents are lifestyle and fashion, art and culture, health and quality of life, nightlife and dining, celebrities and jet set gossip, horoscope, tourism and environment, history, sport and recreation, woman issues, automobile, information and technology, novels, job classified, and shopping. Moreover, there are three proper styles: modern, chic, and natural styles. Each style has its distinctive elements of layout design as follows. Firstly, regarding the modern style, the gradation pattern of composition is a key element to grab attention from the readers by applying different structures leading to the focal point. This also creates a dynamic movement. Few numbers of dark color tones can be paired with a wide variety of bright tones. The curve and round structures can be applied to the Thai font characters with harmonious size and consistent strokes. This can be perceived as humble and noble looks. Secondly, regarding chic style, the composition with a clear distinctive scale together with rhythmic repetitive pattern can draw reader’s attention. Various vivid and bright tones can be used with similar color tones. The round structures can be applied to the Thai font characters with light strokes and consistent lines. Finally, regarding natural style, the composition with rhythmic patterns and movement can create a point of interest noticeably with a harmonious arrangement. Restrictive range of warm color tones as appeared in the natural atmosphere can be used with descending color tones to present the harmonious perception. Free formed Thai fonts with inconsistent stroke are suitable for the natural style.